An enantiopure N,N,O heteroscorpionate ligand derived from (-)-menthone - Bleifuß, Sascha; Hofmann, Fabian; Burzlaff, Nicolai (Zeitschrift für Anorganische und Allgemeine Chemie, 2013)
A new enantiopure heteroscorpionate ligand HOPhbpm (2) was synthesized in a one-pot synthesis. Ligand 2 was obtained in a pyridine-catalysed Peterson rearrangement starting from menthopyrazole, thionyl chloride, and salicylaldehyde. The evidence of κ-coordination of the ligand was shown by the formation of a tetrahedral zinc complex [Zn-κ-(OPhbpm)CH] (3) as well as an molybdenum complex [Mo-κ-(OPhbpm)O Cl] (4). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.